Attachments to parents, psychological well-being and life aspirations of children in selected coastal communities. - Araneta, Czarinnah; Suyo, Jee Grace (2005.)
This study examined the level of attachment to parents and psychological well-being of the children and likewise the life aspirations of these children in selected coastal communities., Twenty-one males (21) and thirty-one (31) females with 12-16 years of age participated in this study. Two scales sere used to rate the attachment to parents and psychological well-being of the respondents and an interview guide to know the life aspirations of the children. It was found that the children of coastal communities generally have a positive psychological well-being and high level of attachment to parents. The participants expressed their top three goals in life - finishing studies, life prosperity and service to God. They wanted to find high paying professional jobs and help in the income of their family. They also wished to live prosperously in a clean and peaceful community.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Children -- Coastal Communities